2013
DOI: 10.4081/ija.2013.e22
|View full text |Cite
|
Sign up to set email alerts
|

Growth and yield promoting effect of artificial mycorrhization combined with different fertiliser rates on field-grown tomato

Abstract: Combination of plant inoculation with a commercial mycorrhizal formulation with half or full fertiliser application rates was evaluated for the effects on plant growth and yield and mycorrhization occurrence throughout two consecutive field tomato crops in southern Italy. Mycorrhizal formulation was inoculated on tomato seedling roots both in the nursery and after transplant. Inoculated tomato seedlings were significantly larger than non-inoculated seedlings less than 30 days after the first inoculation in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
1
15
0
1
Order By: Relevance
“…The supplementary mycorrhization and bacterial inoculation act towards stimulating the development of levels 1 and 3 of the plants, as reported before in other studies (Candido et al, 2013;Candido et al, 2015;Kim et al, 1997). Among the tested fertilisers, the bacterial inoculum had the lowest effect over the development with a gradient towards the Hostati variety and both of them are integrated in the interaction variety-treatment complex.…”
Section: Discussionsupporting
confidence: 74%
“…The supplementary mycorrhization and bacterial inoculation act towards stimulating the development of levels 1 and 3 of the plants, as reported before in other studies (Candido et al, 2013;Candido et al, 2015;Kim et al, 1997). Among the tested fertilisers, the bacterial inoculum had the lowest effect over the development with a gradient towards the Hostati variety and both of them are integrated in the interaction variety-treatment complex.…”
Section: Discussionsupporting
confidence: 74%
“…AMF symbiosis can exert positive effects on crop production [13][14][15][16] and improve plant tolerance to abiotic stresses [17][18][19][20][21] such as drought and salinity. Possible AMF-mediated adaptation mechanisms inducing plant tolerance to saline conditions [22] include: (1) nutrient uptake improvement, especially phosphorus (P) [23][24][25]; (2) accumulation of soluble sugars into the roots [26]; (3) K + /Na + ratio adjustment [27,28]; and (4) antioxidant enzymatic activities [29].…”
Section: Introductionmentioning
confidence: 99%
“…Tomato, with a production of about 164 million tonnes worldwide in 2013, represents one of the most important crops at present. Both growth and yield of tomato are reported to be promoted by various beneficial bacterial strains such as Pseudomonas fluorescens strain 63‐28, Bacillus fortis IAGS162 and Bacillus subtilis IAGS174, Burkholderia tropica strain MTo‐293 and Gluconacetobacter diazotrophicus , as well as for mycorrhiza or the combination of two …”
Section: Introductionmentioning
confidence: 99%
“…also showed a positive effect of non‐mycorrhizal fungal root endophytes on tomato fruit yield and quality. In some cases, it was observed that AMF had a positive effect on plant growth but the quality parameters of tomato fruit were not significantly affected by plant AMF inoculation . In general, tomato quality is impacted by both variety and growth conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%